Eliminasi Arus Inrush Transformator Pada Beban Motor Induksi 3 Fasa Menggunakan Metode Pre–Insertion Resistor - Wahyuni Martiningsih; Herudin Herudin; Ponco Windianto (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2018)
Transformer is the most widely used electromagnetic induction equipment in the electrical system. When the transformer is connected to a voltage source it will happen an undesirable phenomenon that is inrush current. The incidence of inrush current in the transformer can reduce the life of the transformer because large currents will enhance the performance of the transformer. One method to reduce inrush current is to use pre-insertion resistor method. This research uses pre-insertion resistor method which is a method with insert resistor on the primary side of transformer with time 0.18 second. The resistor used in the pre-insertion resistor method serves as a current buffer when the process of energizing the transformer. This research uses Matlab Rb2014a software to know the inrush current of transformer. The result of the transformer simulation test using pre-insertion resistor method, the inrush current is reduced by 29% for the 710 kW motor load capacity, with the motor load capacity of 1420 kW reduced inrush current of 30%. Furthermore, with a load capacity of 2130 kW motor, the inrush current is reduced by 28% and for the motor load capacity 3550 kW reduces the current by 27%.